Worldwide destinations casebook : the geography of travel and tourism / Brian G Boniface, Chris Cooper - Boniface, Brian G
"Worldwide destinations casebook provides 36 comprehensive case studies of international tourism destinations. A companion text to the core textbook Worldwide destinations, 4th ed., these cases contextualize the learning and provide real life illustrationsof the theories covered"--Page 4 of cover.